Association between air pollution and primary liver cancer in European and east Asian populations: a Mendelian randomization study - Sun, Mengting; Gao, Ming; Luo, Manjun; Wang, Tingting; Zhong, Taowei; Qin, Jiabi (Frontiers in Public Health, 2023)
Purpose The incidence of primary liver cancer is increasing year by year, with environmental factors playing a non-negligible role. At present, many studies are still disputing whether air pollution is associated with primary liver cancer incidence, and it is difficult to draw causal inferences. Therefore, in this study, we used two-sample Mendelian randomization (MR) to assess the causal relationship between air pollution (including PM2.5, PM2.5–10, PM10, nitrogen dioxide and nitrogen oxides) and primary liver cancer risk and its related biomarkers (Alpha-fetoprotein, Osteopontin, Glypican-3 and Arginase-1). Patients and methods We used large-scale publicly available genome-wide association studies (GWAS) summary data to conduct MR analyses of European and East Asian populations. Inverse variance weighted (IVW) method was used as the main analysis method, and weighted median model, MR-Egger, simple model and weighted model methods were selected for quality control. Heterogeneity was checked by the Cochran’s Q test. The MR-Egger regression and the MR-PRESSO global test detect pleiotropy. The sensitivity analysis was performed using the leave-one-out method. Results Between air pollution and primary liver cancer in either European (PM2.5: p = 0.993; PM2.5–10: p = 0.833; PM10: p = 0.257; nitrogen dioxide: p = 0.215; nitrogen oxides: p = 0.614) or East Asian (PM2.5: p = 0.718; PM2.5–10: p = 0.362; PM10: p = 0.720; nitrogen dioxide: p = 0.101; nitrogen oxides: p = 0.760) populations were found no statistical association. Notably, there was a causal relationship between nitrogen oxides and Arginase-1, a biomarker associated with hepatocellular differentiation, statistically significant associations remained after deletion for single nucleotide polymorphisms (SNPs) associated with alcohol intake frequency, Body mass index (BMI) and cancers (Beta: 4.46; 95%CI: 0.83–8.08; p = 0.015). There was no heterogeneity or pleiotropy in the results. Conclusion This MR study found no evidence to support a causality between air pollution and primary liver cancer in European and East Asian populations, but nitrogen oxides may affect hepatocellular differentiation.